Developing social accountability in 1styear medical students: A case study from the Nelson R Mandela School of Medicine Durban South Africa - S Knight; J van Wyk; T Dlungwane; S Glajchen (African Journal of Health Professions Education, 2016)
Background. Medical schools need to be more socially accountable. The Making a Difference group community service activity (MaD), which is part of the 1st-year medical curriculum at the University of KwaZulu-Natal, Durban, South Africa, aims to make students more responsible, responsive and accountable to community needs. Small groups of students engage with an organisation of their choice that works with a disadvantaged community. They spend 16 hours in appropriate community service, which includes an HIV and AIDS education activity.Objective. To describe and categorise the MaD process of developing social accountability in medical students.Methods. This case study draws on routinely collected administrative and qualitative data obtained from reflective journals kept by each student. Adocument analysis was undertaken of the posters produced by each group that described their reciprocal learning from this experience. Ethical approval for the ongoing evaluation of the undergraduate programme was obtained.Results. The MaD gave students exposure to authentic experiences through socially accountable activities. Enabled by the structured and stepwise MaD approach, groups demonstrated responsibility in identifying and engaging a local community. They developed a simple plan of action that was responsive to community needs. At each stage, they demonstrated accountability to the various stakeholders. Students reflected on the social determinants of health and disease and described MaD as a ‘humbling and huge learning experience’.Conclusion. Through MaD, 1st-year medical students engaged in practical, socially accountable activities with members of disadvantaged communities.They developed some understanding of a population perspective on health and the social determinants that influence health and disease in a community.